A new species of Monanthotaxis from Gabon with a unique inflorescence type for Annonaceae - Hoekstra, Paul H.; Chatrou, Lars W.; Wieringa, Jan J. (Phytotaxa, 2014)
Monanthotaxis paniculata, a new species endemic to Gabon, is described. This species differs from all known Annonaceae by a unique panicle-like inflorescence type.